Effect of water potential and host defense on the growth of Amylostereum areolatum and A. chailletii, fungal symbionts of siricides, and study of wood associated mycobiota of conifers in Patagonia, Argentina. - López, Sofía N; Greslebin, Alina G; González, Silvia B; Pildain, María Belén (Bosque (Valdivia), 2017)
Amylostereum areolatum and A. chailletii are fungal symbionts of wood-boring wasp Sirex noctilio and Urocerus gigas, respectively. Pinus species are susceptible to the S. noctilio - A. areolatum pathosystem, and in Patagonia, Argentina, it was found that the felled wood of Pseudotsuga menziesii can be attacked by U. gigas and its symbiont. This study evaluated the relationship of A. areolatum, A. chailletii and water potential (ψ0), the primary defense of Pinus ponderosa and P. menziesii, and endophytic mycobiota associated to the wood of both conifers. The different ψ0 were generated by variations in the osmotic potential; constitutive oleoresins of the bark and sapwood of both softwoods were extracted and characterized by GC and GC-MS and the effect of differential and majority compounds on growth of both fungi were assessed; the mycobiota was analyzed from isolates of the sapwood of healthy plants. It was observed that the growth of both fungi is significantly affected by the decrease of ψ0 and that A. chailletii grew faster than A. areolatum under lower ψ0. Oleoresins had a negative effect on the growth of both fungi with no differences between conifers. Hormonema dematioides was the most common endophyte on P. menziesii; this fungus is characterized by its influence on the growth of other fungi and appears as a variable to be considered in setting of S. noctilio - A. areolatum pathosystem.